Effect of teaching by constant practice and varied practice in different distance for some tennis skills and retention - Hussein, shilan (Journal of Physical Education, 2009)
The study objective was to know the effect of teaching in constant practice and varied practice for some tennis skills , the objects were (30) students enrolled in second stage , training department in physical education college at University of Sulimany . The objects were divided in three groups equally , (10) students in each group , The first one used ordinary teaching , second one used constant practice, third one used varied practice for learning forehand and backhand tennis skills , The result revealed that all of the group had effect on learning the skills , and the best group was varied practice , the best group on retention was second group (Constance practice )